(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The structure of the land fund of Ukraine is analyzed in the article. The condition of land relations and land tenure of Rivne and Volyn oblasts, on the basis of the comparison, are investigated in the article. The considerable numbers of land tenure problems of these oblasts are determined. The directions of their ecologization with the aim of sustainable land tenure ensuring.